Knowledge about attention-deficit/hyperactivity disorder among primary schoolteachers in Sharjah, UAE - Sara Saad; Farida Aljanahi; Saravanan Coumaravelou; Ammar Agha; Muna Alsamiri; Sajad Allami (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Teachers' knowledge and awareness about the signs and symptoms, behavioral problems, and treatment are imperative to handling children with attention-deficit/hyperactivity disorder (ADHD) in the school. This study aimed to assess the level of knowledge about ADHD among primary schoolteachers in Sharjah, UAE. MATERIALS AND METHODS: In this cross-sectional study, a convenient sampling method was used to collect data from 239 teachers working in private schools and 25 teachers working at the public schools in Sharjah. A self-administered questionnaire was used to measure the sociodemographic characteristics and the Knowledge of Attention-Deficit Disorders Scale was used to measure the knowledge about ADHD. Data were analyzed using both descriptive and inferential methods. RESULTS: Private schoolteachers have more knowledge about ADHD than public Schoolteachers (P = 0.016). Teachers obtain information about ADHD through educational workshops (32%), social media (23%), friends and relatives (12%), TV and radio (9%), scientific journals (8%), campaigns (7%), and other sources (9%) such as the Internet, lectures, personal experience, and reading. Most of the teachers (56.3%) have knowledge about the signs and symptoms of ADHD, whereas teachers' knowledge about the associated features and treatment of ADHD is 34.4% and 34.1%, respectively. CONCLUSION: Teachers' level of knowledge about ADHD-associated features and treatment was inadequate in Sharjah. Hence, enhancing knowledge about ADHD by providing various training workshops and conducting social events, and campaigns are warranted to enhance their knowledge on ADHD.